Pengaruh Elektroterapi dan Termoterapi secara in Vitro terhadap Eliminasi Onion yellow dwarf virus - Siti Shofiya Nasution; Diny Dinarti; Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2018)
Infection of Onion yellow dwarf virus (OYDV) are reported causing problems in garlic production. Planting virus-free bulbs might help reduce viral disease incidence in the field. This research was aimed to develop method for eliminating OYDV from garlic bulbs using combination of electrotherapy (0, 5, 10, 15, and 20 mA each for 10 minutes) and thermotherapy (23, 28, 33, 38°C each for 4 weeks). Two garlic cultivars, i.e. Sangga Sembalun and Lumbu Hijau were used as seed bulbs for OYDV elimination tests. Virus infection was confirmed using transcription-polymerase chain reaction (RT-PCR).  The result showed that thermotherapy at 33 °Cwas the best method to eliminate OYDV in garlic although the efficiency was not the same for all cultivars. The efficiency reached up to 60% for cv. Lumbu Hijau, whereas for cv. Sangga Sembalun only reached up to 40%. Electrotherapy alone or in combination with thermotherapy were not able to produce OYDV-free plantlets.